The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2020
DOI: 10.1016/j.ausmj.2020.06.014
|View full text |Cite
|
Sign up to set email alerts
|

Consumers’ Resistance to Digital Innovations: A Systematic Review and Framework Development

Abstract: Consumer resistance is one of the major causes of failure of any innovation. Despite rising academic interest, the non-adoption of digital innovation or consumer resistance has received less scholarly attention as compared to the factors driving the adoption of digital products and services. The existing research on consumer resistance is also in siloes, running across multiple verticals, spanning from resistance to green products to the Internet of things (IoT). The current study provides a systematic review … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
141
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 192 publications
(177 citation statements)
references
References 75 publications
(196 reference statements)
3
141
0
1
Order By: Relevance
“…As it is often the case with new and emerging technologies, individuals continue to have important reservations due to the significant levels of risk and uncertainty associated with those novelties (Seegebarth et al, 2019). Resistance, anxiety, and ambivalence toward new technologies represent important aspects of the success and adoption of those technologies (Talwar et al, 2020). Research showed that some people tend to prefer human recommendations over those made by statistical models (Castelo et al, 2018; Dietvorst et al, 2015; Longoni et al, 2019).…”
Section: Theoretical Framework and Predictionsmentioning
confidence: 99%
“…As it is often the case with new and emerging technologies, individuals continue to have important reservations due to the significant levels of risk and uncertainty associated with those novelties (Seegebarth et al, 2019). Resistance, anxiety, and ambivalence toward new technologies represent important aspects of the success and adoption of those technologies (Talwar et al, 2020). Research showed that some people tend to prefer human recommendations over those made by statistical models (Castelo et al, 2018; Dietvorst et al, 2015; Longoni et al, 2019).…”
Section: Theoretical Framework and Predictionsmentioning
confidence: 99%
“…Hence, the concept of an AI‐powered avatar will provide a competitive edge to the gamer in terms of CUST, interactivity, and enjoyment. IDT can further offer innovative characteristics to gamers who wish to adopt new technology (Rogers, 2010; Talwar et al, 2020). This study of AI‐powered avatar with IDT can give consumers insights into how they perceive this phenomenon and how ready they are to adopt it.…”
Section: Literature Review and Theoretical Frameworkmentioning
confidence: 99%
“…The present study aims to address the research gaps in the literature on the use of BDA in healthcare by conducting a systematic literature review (SLR) (Dhir et al 2020;Tandon et al 2020;Talwar et al 2020). SLRs have been recognised for their ability to summarise valuable knowledge about a topic of importance (Dhir et al 2020;Talwar et al 2020) and to guide future research on the topic (Dhir et al 2020;Talwar et al 2020). This SLR aims to address four research questions (RQs) as follows: RQ1.…”
Section: Introductionmentioning
confidence: 99%